Staircase modulation improvement to balance output power of stages of cascade H-bridge multilevel inverter. (October 2022) - Sedaghati, Alireza; Horrillo-Quintero, Pablo; Sánchez-Sáinz, Higino; Fernández-Ramírez, Luis M.
Highlights: Introduction of an efficient algorithm by solving a random optimization problem. Determination of optimal switching pattern statically to balance the power between stages. Faster calculation and simpler implementation of the proposed algorithm than available in the literature. Mathematical analysis and comparison discussion of the proposed algorithm with different techniques. Minimization of the power deviation between stages as much as possible in parallel with the THD decreasing. Abstract: In this study, different methods are investigated to minimize the power imbalance between the stages of a cascade H-bridge (CHB) multilevel inverter (MLI). First-in-first-out (FIFO) and first-in-last-out (FILO) are two common staircase-modulation (SCM) methods. A CHB-MLI with FIFO modulation, even with the same conduction times, cannot distribute power equally between the stages. A new algorithm is presented in this study to balance the power between the inverter stages. This is important to increase the lifetime of the PV sources that feed the inverter. To implement the new algorithm, all possible switching patterns based on the angles obtained from the nearest level of control (NLC) method are defined as the sample spaces of random variables. Subsequently, a random vector is defined for a set of random variables, and an optimization problem with finite and discrete solutions is applied. This algorithm is effectively used to minimize the power imbalance between the stages, even in impedance loads, from the purely inductive to the pure capacitive range. In addition, with slight changes in the switching angles, the operation of the stages and the inverter efficiency increases. Finally, the simulation and experimental results confirm the validity and practicality of the proposed modulation. Graphical abstract: Image, graphical abstract